Informational connectivity: identifying synchronized discriminability of multi-voxel patterns across the brain - Coutanche, Marc N.; Thompson-Schill, Sharon L. (Frontiers in Human Neuroscience, 2013)
The fluctuations in a brain region’s activation levels over a functional magnetic resonance imaging (fMRI) time-course are used in functional connectivity to identify networks with synchronous responses. It is increasingly recognized that multi-voxel activity patterns contain information that cannot be extracted from univariate activation levels. Here we present a novel analysis method that quantifies regions’ synchrony in multi-voxel activity pattern discriminability, rather than univariate activation, across a timeseries. We introduce a measure of multi-voxel pattern discriminability at each time-point, which is then used to identify regions that share synchronous time-courses of condition-specific multi-voxel information. This method has the sensitivity and access to distributed information that multi-voxel pattern analysis enjoys, allowing it to be applied to data from conditions not separable by univariate responses. We demonstrate this by analyzing data collected while people viewed four different types of man-made objects (typically not separable by univariate analyses) using both functional connectivity and informational connectivity methods. Informational connectivity reveals networks of object-processing regions that are not detectable using functional connectivity. The informational connectivity results support prior findings and hypotheses about object-processing. This new method allows investigators to ask questions that are not addressable through typical functional connectivity, just as MVPA has added new research avenues to those addressable with the general linear model.